Clinical profile and commonly used Drugs and their response in chronic headache patients at OPD in DNMCH - Khan, Nurul Amin; Wadud, Shaheen; Islam, Torikul; Chowdhury, Asif Masud; Banik, Shyamal Chandra (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Headache is the most commonest presentation in Neurology Outpatient Department. Headache patient may present in different ways. It may vary in duration, character, severity, location, associated features, and trigger factors. In our clinical practice many drugs are used for treatment of headache. Responses of those drugs may vary from patient to patient. Objectives: To see the clinical profile of chronic headache patients and commonly used drugs and their responses in those patients. Methodology: It was a descriptive, cross sectional observational study. 100 patients presenting with chief complaints of headache to the Neurology OPD in Dhaka National Medical College Hospital between January 2018 to June 2018 were included. Patients with secondary cause of headache were excluded for the study. Results were tabulated and analyzed. Results: Tension headache was the commonest headache type (72%), followed by migraine headache (28%). Intensity was severe in majority of cases (65%), frequency of headache was 9.5±4.4 (Min 2 -Max 20) times per month with duration of 2.8±1.4 (Min 1-Max 12) days. Bilateral band like pain was the commonest (45%) clinical presentation. Among the associated features, vomiting (86%) and vertigo (56%) were common and journey was the commonest aggravating factor (78%). Commonly prescribed drugs were Amitriptyline (70%) and Propranolol (48%). Drug response was good among 66% patients. Conclusion: Clinical presentation of headache may vary patient to patient. The diversity of headache presentations and response to the drugs need to know very well for accurate diagnosis and management of headache patients. J. Dhaka National Med. Coll. Hos. 2022; 28 (01): 27-30